Bibliometric Analysis: Self-Efficacy Research In High School In One Decades Fin - Resti Ramadhaniyati; Eeng Ahman; Amir Machmud; Nani Sutarni (STKIP Yapis Dompu, 2023)
Self-Efficacy is the belief to do the task and become a determinant in individual development. This study aims to capture the relevant previous research landscape related to Self-Efficacy in senior high schools in the last decade using bibliometric analysis Data taken from the database scopus refined to 90 publications. 2020 has published the most articles compared to other years, namely 17 publications. The trend of citations related to Self-Efficacy in high schools occurred in 2013 with 148 citations. Indonesia, Taiwan and China are the most influential countries in this field. The focus of research related to Self-Efficacy in high schools is, 1) Gender; 2) study achievement; 3) social support. The three parts of the research focus can be used as guidelines for further research that wants to take the theme of Self-Efficacy, especially at the high school level to determine the research focus to be studied.